Custom in Islamic law and theory the development of the concepts of Urf and Adah in the Islamic legal tradition - Shabana, Ayman (Palgrave series in Islamic theology, law, and history, 2010)
This book explores the relationship between custom and Islamic law and seeks to uncover the role of custom in the construction of legal rulings. On a deeper level, however, it deals with the perennial problem of change and continuity in the Islamic legal tradition (or any tradition for that matter).